Has the incidence of brain cancer risen in Australia since the introduction of mobile phones 29 years ago?. (June 2016) - Chapman, Simon; Azizi, Lamiae; Luo, Qingwei; Sitas, Freddy
Highlights: Mobile phone use in Australia began in 1987. Use is now over 90%. Brain cancer incidence between 1982 and 2013 has not increased in any age group except those aged 70–84; in the latter group the increase began in 1982, before mobile phones were introduced. We hypothesize the increases in incidence of brain cancer in the oldest age group are due to improved diagnostic detection. We found no increase in brain cancer incidence compatible with the steep increase in mobile phone use. Abstract: Background: Mobile phone use in Australia has increased rapidly since its introduction in 1987 with whole population usage being 94% by 2014. We explored the popularly hypothesised association between brain cancer incidence and mobile phone use. Study methods: Using national cancer registration data, we examined age and gender specific incidence rates of 19, 858 male and 14, 222 females diagnosed with brain cancer in Australia between 1982 and 2012, and mobile phone usage data from 1987 to 2012. We modelled expected age specific rates (20–39, 40–59, 60–69, 70–84 years), based on published reports of relative risks (RR) of 1.5 in ever-users of mobile phones, and RR of 2.5 in a proportion of 'heavy users' (19% of all users), assuming a 10-year lag period between use and incidence. Summary answers: Age adjusted brain cancer incidence rates (20–84 years, per 100, 000) have risen slightly in males (p < 0.05) but were stable over 30 years in females (p > 0.05) and are higher in males 8.7 (CI = 8.1–9.3) than in females, 5.8 (CI = 5.3–6.3). Assuming a causal RR of 1.5 and 10-year lag period, the expected incidence rate in males in 2012 would be 11.7 (11–12.4) and in females 7.7 (CI = 7.2–8.3), both p < 0.01; 1434 cases observed in 2012, vs. 1867 expected. Significant increases in brain cancer incidence were observed (in keeping with modelled rates) only in those aged ≥70 years (both sexes), but the increase in incidence in this age group began from 1982, before the introduction of mobile phones. Modelled expected incidence rates were higher in all age groups in comparison to what was observed. Assuming a causal RR of 2.5 among 'heavy users' gave 2038 expected cases in all age groups. Limitations: This is an ecological trends analysis, with no data on individual mobile phone use and outcome. What this study adds: The observed stability of brain cancer incidence in Australia between 1982 and 2012 in all age groups except in those over 70 years compared to increasing modelled expected estimates, suggests that the observed increases in brain cancer incidence in the older age group are unlikely to be related to mobile phone use. Rather, we hypothesize that the observed increases in brain cancer incidence in Australia are related to the advent of improved diagnostic procedures when computed tomography and related imaging technologies were introduced in the early 1980s.